STUDY OF BODY MASS INDEX (BMI), BODY FAT PERCENT (%BF), AND WAIST TO HIP RATIO (WHR) IN MALE PHYSICAL EDUCATION STUDENTS - Shabani Mehrzad; Shakerian Saeid; Fatemi Rouholah (Physical Education of Students)
The purpose of this study was to investigate body mass index (BMI), body fat percent (%BF) and waist-hip ratio (WHR) of physical education male students of Shahid Chamran University and comparison with national and international body composition standards. Material : Subjects were seventy five male students physical education male students of Shahid Chamran University of mean age (23.21±2.78), mean height (174±5.71) and mean weight (70.07±9.43) who were selected randomly. Some of body composition indices were determined with body composition analyzer apparatus (bioelectrical impedance apparatus). Results : Descriptive characteristics of subjects include: body fat percent (19.37±3.62), waist-hip ratio (0.80±0.037) and body mass index (23.18±2.68). To categorize and regulate data we used descriptive analyzes, to calculate Pearson correlation coefficient we used presumption analyzes and to compare the obtained data with national standards we used T-test statistical procedure. There are significant correlations between body mass index and waist-hip ratio (P=0.709, r=0.001), between body mass index and body fat percent (P=0.783, r=0.001) and between body fat percent and waist-hip ratio (P=0.809, r=0.001). There are significant differences between mean body mass index and its national standard (P=0.001), between mean waist-hip ratio and its national standard (P=0.001) and between mean body fat percentage and its national standard (P=0.001). Conclusions : Results revealed that according to national standards of body fat percentage and body mass index of subjects, they were assigned to more than intermediate limitation; it may be due to abnormal nutrition, unregulated exercise or physical activity and heredity.